A guide to teaching information literacy 101 practical tips - Blanchett, Helen; Powis, Chris; Webb, Jo. (London Facet Publishing, 2012)
This easy-to-use book is an invaluable source of inspiration for any librarian involved in teaching information literacy, whether they are new to teaching or experienced but in search of fresh ideas.
Keywords: Information literacy -- Study and teaching